KETAHANAN PANGAN RUMAH TANGGA PETANI DALAM TEKANAN PRODUKSI DAN KEBIJAKAN BANTUAN: ANALISIS LINTAS PROVINSI - Noviar, Helmi; Badli, Saiful; Rizki, Darlin; Zulbaidi, Zulbaidi; Fadhlain, Said (Jurnal Al-Kharaj: Studi Ekonomi Syariah, Muamalah, dan Hukum Ekonomi, 2026)
Household resilience among farming communities remains a critical issue in Indonesia’s agricultural development, particularly amid persistent production constraints and heterogeneous policy interventions across regions. This study aims to examine the relationship between agricultural income, production-related challenges, and various forms of social and agricultural assistance in shaping farm household resilience across Indonesian provinces. The analysis employs data from the 2024 Agricultural Economic Survey (SEP), using provinces as the unit of analysis. The methodological approach combines descriptive statistics, classification of income-based resilience risk, partial correlation analysis, and multiple linear regression estimated using the Ordinary Least Squares (OLS) method. The results reveal substantial heterogeneity in farm household resilience across provinces. Provinces classified as high-risk are predominantly characterized by households in the vulnerable and moderately resilient categories, reflecting structural limitations in agricultural income and access to productive inputs. Regression estimates indicate that consumption-oriented assistance, particularly Village Fund Cash Transfers, has a negative and statistically significant association with the Food Security Index, whereas productive support in the form of subsidized fertilizer exhibits a positive effect, albeit with limited statistical significance. These findings suggest that assistance programs do not automatically enhance farm household resilience; rather, their effectiveness depends critically on the orientation and function of the intervention. The study underscores the importance of regionally differentiated policy approaches that integrate short-term social protection with long-term strategies aimed at strengthening agricultural productivity and income sustainability.